PENGARUH BRAND IMAGE, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KEMBALI PADA PRODUK HIGH END MAKE UP AND SKIN CARE PADA GENERASI MILLENIAL JAKARTA - Oktafalia Marisa M; Janny Rowena (STIE Wiyatamandala, 2019)
Y generation or also called as Millenial Generation are group of the people who born in 1980 – 2000. Milenial life very closes with digital technology or we can call them tech savvy by the nature. One of their distinguished habbit was the frequency of using social media. Aside from culinary, this Millenial Generation also closed with make up and skin care products. Style and appearance become very important for this generation. This habbit also lead them to become very narcissistic and post everything about their life in social media. This research will discuss about Brand Image, Price and Product Quality influence to Repurchase Decision for high end make up and skin care product. The scope of this research is only in Jakarta. The subject of this research is 30 consumers that repeatedly buy the make up and skin care product for their lifestyle. The independent variables are Brand Image, Price and Product Quality. And for dependent variable is Repurchase Decision. This model analyzed using multiple regressions. Purpose of this research is to observe the influence of culture effect, social, personal and psychological aspect to purchase decision of the high end make up and skin care products. Result that obtained in this research is culture effect, social, personal and psychology aspect has influenced to purchase decision of high end make up and skin care product for Millenial Generaion.